EFEKTIFITAS PENGGUNAAN MOBILE BANKING PADA GENERASI Z - Mohammad Zidan RIzaldi (2022)
Payment is an important component in every trade transaction activity, both goods and services. before digital payment technology there were humans transacting using the exchange or barter method, and developing using M-Banking technology. many shops and even klontong stalls already provide a QR code so that it is more effective and efficient. Technology is also developing in the banking world, many bank products are created using technology because they are more efficient. Generation Z is the generation born in 1995-2010. Generation Z has different characteristics from other generations, Generation Z has a character who likes flexible lifestyle technology. respondents, totaling 79 respondents with generation Z status, all of them already have savings accounts and the M-Banking application is on their cellphones, and users of Mobile Banking services from different Bank agencies, based on the results of the questionnaire the majority of respondents using Mobile banking services from Bank BCA . There are 5 indicators that influence the level of effectiveness.